Does Critical Success Factors of KM Mediate the KS-Driven Performance in the Software Sector of Pakistan? - Wasim ul Rehman; Suleyman Degirmen; Faryal Jalil; Muhammad Haris; Tarram Nayyab (Journal of Management and Research, 2021)
This research tends to investigate role of KS practices on overall performance of software sector using critical success factors of KM (i.e. KM process and infrastructure capabilities) as intermediate measures. In this regard, a survey method using the adapted instrument to draw the inference from data collected from software developers.  The parallel multiple mediation model proposed and tested by using Process Macro. The findings of study reveal that KS practices have a significant and positive effect on the overall performance in terms of operational excellence, financial achievement, customer intimacy, product leadership. The results indicate that all the constructs of KM process and infrastructure capabilities partially mediates the relationship between KS practices and performance of software sector. Hence, findings of study support all the suggested hypotheses and draws the inference that KM process and infrastructure capabilities support the theoretical prisms of KBV initiatives.